2011
DOI: 10.1016/j.ymgme.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and pathology in hydroxypropyl-beta-cyclodextin-treated and untreated Npc1−/− mice

Abstract: Lung dysfunction is an important part of the pathology of the neurodegenerative disorder, Niemann-Pick C1 (NPC1). We have studied the pulmonary disease in the Npc1NIH/NIH mouse model. On histology, we find large numbers of alveolar foamy macrophages but no alveolar proteinosis. Lung weight as percent of body weight was markedly increased; using the flexiVent small animal ventilator (SCIREQ, Inc.), we find inspiratory capacity, elastance and hysterisivity to be increased while resistance was not changed. Choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Disrupted copper homeostasis is widespread in all Npc1 −/− mouse tissue types examined, with the most dramatic change of a 170 ± 17% increase in the lungs. It is possible that the copper-induced oxidative stress in the lungs may contribute to the pulmonary abnormalities reported in animal model studies 47, 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted copper homeostasis is widespread in all Npc1 −/− mouse tissue types examined, with the most dramatic change of a 170 ± 17% increase in the lungs. It is possible that the copper-induced oxidative stress in the lungs may contribute to the pulmonary abnormalities reported in animal model studies 47, 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the susceptibility to HPBCD was different between Npc1 +/+ and Npc1 +/ − , and Npc1 −/− mice. Muralidhar et al [15] and Ramirez et al [4] reported that treatment of Npc1 −/− mice with HPBCD had little or no effect on the development of progressive pulmonary disease. Therefore, when evaluating the safety of HPBCD therapy for NPC disease, the difference of NPC1 genotype should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…While there was also a slowing of cerebellar neurodegeneration and an increase in lifespan, systemic 2HPβCD treatment had little to no effect on the development of progressive pulmonary disease [26]. Subsequent studies further demonstrated lack of impact of systemically administered 2HPβCD on a number of parameters of lung function and pathology in the Npc1 −/− mouse [27]. There is nothing intrinsically different about UC sequestration in the lungs in NPC1 or NPC2 deficiency because NPC2 replacement therapy in a mouse model of NPC2 disease resulted in a striking reduction in the cholesterol content of several organs including the lungs [28].…”
Section: Introductionmentioning
confidence: 99%